International Experience of Organization and Activities of Forensic Expert Institutions - V. V. Chumak (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article studies international experience of the organization and activities of forensic institutions on the example of such countries as Germany, France, the Netherlands, Czech Republic and the United Kingdom. The legislative features of the functioning of forensic institutions and the regulation of the legal status of experts are noted. It is determined that regardless of the departmental subordination of forensic institutions, their activities are based on international standards.